AICCRA report: Stakeholders Mapping Arbahajan Ward, Wajir County - Mukalo, Irene Aloo; Akivaga, Allan (2023)
This report presents the findings of a stakeholder mapping conducted in Arbahajan Ward from August 17th to 19th, 2023. Stakeholders mapping is a crucial initial step for implementing Participatory Rangelands Management (PRM) and has been undertaken under the auspices of the Livestock and Climate Initiative by RECONCILE in collaboration with ILRI.